Potensi Bakteri Gram Positif dalam Eco-Enzym dari Tumbuhan Lahan Gambut: Inovasi Sumber Belajar Bioteknologi untuk Mengembangkan Kemampuan Penalaran Ilmiah - Elga Araina; Silvita; Saritha Kittie Uda; Melda Andani (Jurnal Penelitian Pendidikan IPA, 2025)
This study aims to observe Gram-positive bacteria in eco-enzymes produced from the fermentation of peatland plants in Central Kalimantan and to analyze their potential as biotechnology learning resources for developing students’ scientific explanation skills. The research employed a descriptive qualitative method through eco-enzyme preparation, bacterial identification using Gram staining, and analysis of the role of observational results in the learning context. The findings revealed four Gram-positive bacteria, namely Staphylococcus aureus, Staphylococcus epidermidis, Bacillus subtilis, and Lactobacillus bulgaricus. The presence of these bacteria demonstrates the active involvement of microorganisms in the fermentation process, which can serve as a concrete example for students to understand biotechnology concepts. These results emphasize that bacterial identification outcomes are not only scientifically valuable but also hold potential as contextual learning resources that support the development of scientific explanation. Through these observational results, students can practice constructing claims, presenting evidence, and connecting them with scientific reasoning. Therefore, this study concludes that exploring Gram-positive bacteria in eco-enzymes derived from peatland plants has the potential to enrich biotechnology learning while simultaneously developing students’ scientific explanation skills.